2014
DOI: 10.1098/rsif.2013.1044
|View full text |Cite
|
Sign up to set email alerts
|

Corruption drives the emergence of civil society

Abstract: Centralized sanctioning institutions have been shown to emerge naturally through social learning, displace all other forms of punishment and lead to stable cooperation. However, this result provokes a number of questions. If centralized sanctioning is so successful, then why do many highly authoritarian states suffer from low levels of cooperation? Why do states with high levels of public good provision tend to rely more on citizen-driven peer punishment? Here, we consider how corruption influences the evoluti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 29 publications
2
28
0
2
Order By: Relevance
“…In this context, it may also interesting to study how the efficiency of central punishment institutions is undermined by bribery and corruption 87 . In the context of homogeneous groups, corruption possibilities can lead to a large decrease in public good provisioning, with the exact welfare losses depending on the cultural background of a society, the implemented transparency rules, and the extent to which leaders themselves are invested in the public good 88 .…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it may also interesting to study how the efficiency of central punishment institutions is undermined by bribery and corruption 87 . In the context of homogeneous groups, corruption possibilities can lead to a large decrease in public good provisioning, with the exact welfare losses depending on the cultural background of a society, the implemented transparency rules, and the extent to which leaders themselves are invested in the public good 88 .…”
Section: Discussionmentioning
confidence: 99%
“…52 While punishment can solve the original dilemma of cooperation, the effectiveness of punishment in promoting cooperation has been challenged by recent theoretical research showing that the existence of corruption where defectors bribe corrupt officials to avoid punishment can destroy the positive consequence of costly punishment in cooperation. 1,29,31,35,66 For example, Muthukrishna et al 35 experimentally showed that the possibility of corruption can cause a significant fall in public good provisioning and make empowering leaders decrease cooperative contributions.…”
Section: Introductionmentioning
confidence: 99%
“…Abdallah et al [1], among studies of social behaviour, demonstrate that peerpunishment is more effective than an overly strong centralized punishment in promoting cooperation, if actors are able to bribe centralized authorities.…”
Section: Related Workmentioning
confidence: 99%
“…, C. Second, the agent's origin ('town') is set based on the clan. Towns are divided logarithmically from largest clan (1) to smallest (C): clan 1, the largest clan, has approximately 1 2 of the towns; clan 2 has approximately 1 2 of the remainder, and so on, with the constraint that every clan has at least one town. If the agent is to live in one of its clan's towns (based on chance), the town is assigned randomly among them; otherwise the town is assigned randomly from all the other clans' towns.…”
Section: Basic Modelmentioning
confidence: 99%
See 1 more Smart Citation